A Juridical Analysis of PPATK’s Dormant Account Blocking Policy: An Examination of Authority and Legal Protection for Account Holders - Zuhair Huda (Yayasan Cerdas Pedia Indonesia, 2025)
This study offers a comprehensive juridical analysis of Indonesia’s Financial Transaction Reports and Analysis Center (PPATK) policy to block dormant bank accounts, assessing its legality, constitutional compliance, and proportionality. Employing a normative–descriptive legal research method, the analysis draws on primary sources (Law No. 8/2010 on Money Laundering, the 1945 Constitution, banking and consumer-protection statutes) and secondary sources from Scopus-indexed literature on Financial Intelligence Unit (FIU) governance, administrative law, and constitutional rights. Findings demonstrate that PPATK exceeded its statutory authority under Law No. 8/2010 by imposing mass suspensions on 122 million accounts without individualized suspicion of criminal activity, thereby violating the ultra vires doctrine in Law No. 30/2014 on Government Administration. The policy also infringed Articles 28D(1) and 28G(1) of the Constitution by failing to provide pre-deprivation due-process safeguards or narrowly tailored measures, instead relying on post-deprivation remedial procedures. A proportionality assessment, grounded in administrative-law doctrine, shows the blocking policy lacked appropriateness, necessity, and proportionality stricto sensu, as less restrictive alternatives (enhanced KYC, targeted investigations, judicial review) were available. Despite PPATK’s claims of a 70 percent reduction in online gambling transactions, the legal deficiencies rendered the policy unsustainable, leading to its presidentially mandated reversal. Comparative analysis with international FIU best practices underscores the need for statutory amendments to clarify FIU powers, mandatory judicial oversight, and independent accountability mechanisms. This research contributes to Scopus-indexed scholarship by empirically validating theoretical concerns about FIU overreach, offering policy recommendations to balance effective financial crime prevention with constitutional and consumer-protection imperatives.